2005
DOI: 10.5713/ajas.2005.686
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Intersequence Pauses, Laying Persistency and Concentration of Prolactin during the Productive Period in White Leghorn Hens

Abstract: Prolactin is considered to influence the taking of pauses in between ovulatory sequences in White Leghorn hens.Therefore modulating concentrations of prolactin using bromocriptine -a dopamine agonist during early life (17 to 36 weeks of age) could overcome the inhibitory effects of high concentration of prolactin on ovarian activity. The effect of modulation of prolactin concentration on egg production, sequence length and inter sequence pauses were studied by analyzing the oviposition records from 19 to 72 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Clutch size ( CS ), the number of eggs laid on successive days by a hen, was calculated as the total number of eggs laid within a period divided by the number of sequences recorded ( Blake and Ringer 1987 ). The length of pause ( LP ) was determined following Reddy et al. (2005) and was calculated by dividing total number of pause days with number of pauses recorded within a period for each hen.…”
Section: Methodsmentioning
confidence: 99%
“…Clutch size ( CS ), the number of eggs laid on successive days by a hen, was calculated as the total number of eggs laid within a period divided by the number of sequences recorded ( Blake and Ringer 1987 ). The length of pause ( LP ) was determined following Reddy et al. (2005) and was calculated by dividing total number of pause days with number of pauses recorded within a period for each hen.…”
Section: Methodsmentioning
confidence: 99%
“…This may explain the cause for longer sequences and reduced laying pauses in the treated birds. However, the occurrence of more than 8 days (more than 11 days by Reddy et al, 2005; more than 8 days by Reddy et al, 2006) of laying pauses in birds of both groups may be due to the genetic constitution of individual birds. In the present study the treatment with bromocriptine through oral feeding, during laying was able to control egg production in indigenous hens.…”
Section: Laying Pausesmentioning
confidence: 99%
“…The PLR and PRLR genes are expressed in many tissues including the hypothalamus, ovary and oviduct [56,57], and mediate the formation of egg quality [58]. PRL is generally considered to be a key factor in the onset and maintenance of broody behaviour in birds, and it has been well established that the elevated plasma PRL inhibits gonadotropin release, ovum development and ovulation, resulting poor laying performance and even complete cessation of egg production in laying hens [59][60][61][62]. Transcriptome studies have also revealed PRL is associated with egg production performance in chicken hypothalamic-pituitary-ovarian axis [63,64].…”
Section: Discussionmentioning
confidence: 99%